An innovative landslide risk assessment system: application to highway embankments - Pantelidis, Lysandros (My University, 2011)
In this paper a landslide risk assessment system referring to highway embankments is proposed. The system in question consists of three stages, a) the quantitative attribution of the failure hazard of embankments, b) the calculation of geometric characteristics of a possible failure and c) the quantitative attribution of consequences. As regards to the first stage, the failure hazard derives from the drained condition of embankments and the influence that climatic conditions have on their stability; the latter being the most common landslide-triggering factor. The second stage is based on existing methods and models; allowing for application in Highway Engineering the proposed system provides an assessment of the failure extent with regard to roadway elements. Finally, the third stage fully distinguishes the consequences to traveler's safety from those to traffic flow. Correspondingly, there are two risk values, where, the highest one is chosen every time. Based on the last, an alertness condition is assigned accompanied by recommended actions.
Keywords: Geohazards; Risk management; Landslides; Highways and roads; Embankments